Analisis Pengendalian Kualitas Produk Tiang Listrik dengan Metode Seven Tools dan FMEA (Failure Mode Effect Analysis) di PT XY - Basjir, Mochammad; Kresna Agung Yudhistira; Unung Lesmanah; Nur Robbi; Suhartini (Journal of Research and Technology, 2024)
PT XY, a precast concrete manufacturer, especially for electric poles, faces product quality problems in the form of defects, which harm quality, management, and production costs. This study aims to identify the root causes of defects and provide improvement solutions using the Seven Tools and Failure Mode and Effect Analysis (FMEA) methods. FMEA is used to identify potential and risk of failure and to formulate priority improvement actions. The results of the study showed three main types of defects: porous fins (53.53%), skin sticking (39.56%), and mottled (6.92%). The causal factors include methods, materials, humans, and machines/tools. FMEA analysis produces the highest Risk Priority Number (RPN) for porous fins (192) caused by imprecise molds (machine/tool ​​factors). The recommended solution is to inspect and repair the moulds periodically. Skin sticking defects have an RPN of 210, caused by poor oil quality (material factors); replacing the oil with an oil-based type is the solution. Mottled defects with an RPN of 144 are caused by the low slump of the casting mixture; the solution is to guide the mixing of raw materials according to standards. This study provides specific recommendations to reduce defects in electric pole products at PT XY, focusing on mould improvement, replacement of oil types, and standardization of raw material mixing.